Karen Bakker, «The sounds of life: how digital technology is bringing us closer to the worlds of animals and plants», Princeton University Press, Princeton and Oxford 2022, 354 pp. (Balthazar, 2023)
Recensione del volume «The sounds of life: how digital technology is bringing us closer to the worlds of animals and plants» (Princeton University Press, 2022) di Karen Bakker.